Gadolinium retention in gliomas and adjacent normal brain tissue: association with tumor contrast enhancement and linear/macrocyclic agents - Kiviniemi A.; Gardberg M.; Ek P.; Frantzén J.; Bobacka J.; Minn H. (Springer Verlag, 2025)
Purpose: To quantitate gadolinium deposits in gliomas and adjacent normal brain specimens, and to evaluate their association with tumor contrast enhancement and the type of gadolinium-based contrast agent (GBCA) used.
Methods: A total of 69 patients with primary glioma who underwent contrast-enhanced magnetic resonance imaging (MRI) prior to surgery were included in this retrospective study. Gadolinium was measured from histologically viable tumor, normal brain, and necrosis within the sample, when available, using inductively coupled plasma mass spectrometry (ICP-MS). Tumor contrast enhancement was categorized as none, minimal, or noticeable. Differences in gadolinium deposits by contrast enhancement and GBCA type were assessed.
Results: Seven patients received linear GBCA and 62 macrocyclic, respectively. At the time of surgery, gadolinium deposits were detected in 39 out of 69 (57%) tumor samples, 8 out of 13 (62%) normal brain, and 12 out of 14 (86%) necrotic specimens. Gadolinium was detected in both enhancing and non-enhancing tumors, but was greatest in gliomas with noticeable enhancement (p = 0.02). Administration of linear agents gadodiamide and gadopentetate dimeglumine resulted in significantly higher tumor gadolinium relative to macrocyclic gadoterate meglumine (p < 0.01 and p < 0.05, respectively). Normal brain and necrosis also showed higher gadolinium after exposure to linear gadodiamide (both p < 0.05). In multivariate regression, GBCA type (linear/macrocyclic) was the most powerful predictor of tumor gadolinium retention (p < 0.001).
Conclusion: Gadolinium can be detected in both enhancing and non-enhancing gliomas, neighboring normal brain, and necrosis. Gadolinium retention is higher after exposure to linear GBCAs compared with the macrocyclic gadoterate meglumine.